PRELIMINARY EVALUATION OF LOCAL SITE CONDITON IN YOGYAKARTA BASIN - Tun Naing; Subagyo Pramumijoyo; Hiroshi Kawase (Journal of Applied Geology, 2015)
The Yogyakarta Basin can be defined as NE – SW elongated depression zone of 20 km in width and 45 km in length, trending from Yogyakarta City in north to the Indian Ocean in south. The local geologic and soil conditions have a great influence on the intensity of ground motion and earthquake damage. Local site effects play an important role in earthquake-resistant design and must be accounted for on a case by case basis. Local site conditions can profoundly influence all of the important characteristics such as amplitude (peak acceleration, velocity and displacement), frequency content and duration of strong ground motion. The extent of their influence depends on the geometry and material properties of subsurface materials. Therefore, subsurface investigation was carried out through nine boreholes throughout the basin. Based on drill-logs, collected samples and laboratory test results, the subsurface soil profiles of nine areas in the basin are simplified for future strong ground motion simulation. Five subsurface layers in Tampuran, Krajan areas and six subsurface soil layers in Watu, Jl. Parangtritis, Wijirejo areas and seven layers in Jl. Parangtritis, Karang Semut, Bambang Lipuro areas and eight layers in Pranti area, have been simplified and the geotechnical properties of each layer have been evaluated as well. Keywords: Basin, Yogyakarta, depression, ground motion, earthquake.